Δ‐Myrtoxin‐Mp1a is a Helical Heterodimer from the Venom of the Jack Jumper Ant that has Antimicrobial, Membrane‐Disrupting, and Nociceptive Activities. (9th June 2017) - Dekan, Zoltan; Headey, Stephen J.; Scanlon, Martin; Baldo, Brian A.; Lee, Tzong‐Hsien; Aguilar, Marie‐Isabel; Deuis, Jennifer R.; Vetter, Irina; Elliott, Alysha G.; Amado, Maite; Cooper, Matthew A.; Alewood, Dianne; et al.
Abstract: Δ‐Myrtoxin‐Mp1a (Mp1a), a 49‐residue heterodimeric peptide from the venom of Myrmecia pilosula, comprises a 26‐mer A chain and a 23‐mer B chain connected by two disulfide bonds in an antiparallel arrangement. Combination of the individual synthetic chains through aerial oxidation remarkably resulted in the self‐assembly of Mp1a as a homogenous product without the need for directed disulfide‐bond formation. NMR analysis revealed a well‐defined, unique structure containing an antiparallel α‐helix pair. Dual polarization interferometry (DPI) analysis showed strong interaction with supported lipid bilayers and insertion within the bilayers. Mp1a caused non‐specific Ca 2+ influx in SH‐SY5Y cells with a half maximal effective concentration (EC50 ) of 4.3 μm . Mp1a also displayed broad‐spectrum antimicrobial activity, with the highest potency against Gram‐negative Acinetobacter baumannii (MIC 25 nm ). Intraplantar injection (10 μm ) in mice elicited spontaneous pain and mechanical allodynia. Single‐ and two‐chain mimetics of Mp1a revealed functional selectivity.